Foreign Capital Flows, Financial Development and Growth in Sub-Saharan Africa (2015)
This paper investigated how financial development influences the relationship between foreign direct investment (FDI) and economic growth in selected Sub-Saharan Africa (SSA) countries. This study considered three alternative measures of financial development (FD) and their impacts on the FDI-growth linkage. It also explored the possibility of nonlinearities in the tripartite relationships. The results showed a positive influence of FDI on economic growth. Financial system development also had growth-promoting impact in the presence of FDI flows. Interestingly, these findings remained robust when potential endogeneity was accounted for using a well known instrumental variable (IV) estimator. Digging deeper, the findings also supported the existence of non-linearities in the role of FD in the FDI-growth association. In policy terms, these SSA countries will reap more growth benefits from foreign capital flows especially if financial reforms are sustained.